1992
DOI: 10.1111/j.1744-7348.1992.tb03438.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of closterovirus‐like particles associated with a whitefly‐transmitted disease of sweet potato

Abstract: SummaryA virus causing sunken veins on ‘Georgia Jet’ sweet potato, and yellow brittle leaves and stunting on Ipomoea setosa, was purified and a specific antiserum was prepared. Flexuous particles with a normal length of 850 nm and a diameter of 12 nm with an open helical structure typical of closteroviruses were observed. The virus particle protein has an apparent mol. wt of c. 34 kD. Double‐stranded RNA isolated from SPSVV‐infected I. setosa and subjected to electrophoresis in agarose consisted of one major b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 20 publications
0
38
1
Order By: Relevance
“…SPCSV-m2-47 was isolated from an infected sweetpotato plant grown in the Cañete valley, Peru (Gutiérrez et al, 2003). SPCSV-Is, previously described as SPSVV in Israel (Cohen et al, 1992;Milgram et al, 1996), was kindly provided by Professor Gad Loebestein (The Volcani Center, Bet Dagan, Israel). The isolate of SPFMV (SPFMV-Nam1) used in this study was originally obtained from an infected sweetpotato plant in Uganda and belongs to the EA strain of SPFMV Kreuze et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPCSV-m2-47 was isolated from an infected sweetpotato plant grown in the Cañete valley, Peru (Gutiérrez et al, 2003). SPCSV-Is, previously described as SPSVV in Israel (Cohen et al, 1992;Milgram et al, 1996), was kindly provided by Professor Gad Loebestein (The Volcani Center, Bet Dagan, Israel). The isolate of SPFMV (SPFMV-Nam1) used in this study was originally obtained from an infected sweetpotato plant in Uganda and belongs to the EA strain of SPFMV Kreuze et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…However, SPCSV isolates from Nigeria, Israel and the USA have been found to be related to each other (Hoyer et al, 1996b;Pio-Ribeiro et al, 1996;Vetten et al, 1996) and assigned to the strain WA, named according to the original description of SPCSV as a 'chlorotic stunt'-causing agent in sweetpotatoes in Nigeria, West Africa (Schaefers & Terry, 1976). Closterovirus-like particles were later detected in sweetpotatoes showing chlorotic stunt symptoms in Nigeria (Winter et al, 1992), Israel (Cohen et al, 1992) and Kenya (Hoyer et al, 1996a, b). The virus in these plants was named sweet potato sunken vein virus.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that localization of criniviruses in planta is generally confined to sieve cells (Cohen et al 1992;Hourani and Abou-Jawdah 2003;Medina et al 2003;Winter et al 1992;Wisler et al 1998b;Yamashita et al 1979). To determine whether this is true for CCYV, we performed tissue print analysis, in which a cross-sectioned petiole was blotted on a nylon membrane followed by Each point is the average of the readings from two wells immunostaining, as described by Hourani and AbouJawdah (2003).…”
mentioning
confidence: 99%
“…SPCSV virions were purified from infected plants of I. setosa (10), and RNA was extracted from the virions (36). RNA concentration was determined by absorbance at 260 nm with a UV spectrophotometer.…”
Section: Plant Materials and Virus Isolatementioning
confidence: 99%
“…For instance, SPCSV is phloem limited in sweet potato plants (35) and is transmitted by whiteflies (10,56). In the flexuous filamentous virions, the viral genome of Closteroviridae is encapsidated by two types of coat protein (CP) arranged in a polar configuration (3,21,58).…”
mentioning
confidence: 99%